Caspase-3 and beclin-1 in patients with and without intra-aortic balloon pump after cardiac arrest: Study of apoptosis and autophagy - Firdaus, Isman; Bunga Dewanggi; Kartika, Gloria; Andriantoro, Hananto; Yuniadi, Yoga; Boom, Cindy Elfira; Harimurti, Kuntjoro (Heart Science Journal, 2026)
Background: Ischemic and reperfusion injuries occur during cardiac arrest and after successful resuscitation, potentially triggering apoptosis and autophagy, which can cause irreversible cell damage or death. Beclin-1 and Caspase-3 are proteins that play roles in autophagy and apoptosis pathways. However, it remains unclear whether the insertion of an IABP influences the serum levels of these proteins in patients with cardiac arrest and acute coronary syndrome (ACS). Objective: To investigate the Caspace-3 and Beclin-1 serum levels after Intra-Aortic Balloon Pumps (IABP) in cardiac arrest survivors with ACS. Methods: This is a single-center prospective randomized control trial (RCT) study using an unpaired t-test and a Mann-Whitney U-test to analyze the data (p-value<0.05). Result: This study included sixty subjects: 48 males and 12 females, with a mean age of 60.3 ± 9.85 years. The result showed there’s no significant difference in Beclin-1 and Caspase-3 serum levels before and after the insertion of IABP in both survival and non-survival groups (p=0.676). Caspace-3 serum level was higher in non-survival group. ROC curve analysis showed the caspase-3 level has a predictive value for mortality in cardiac arrest survivors with ACS (p=0.012). Conclusion: IABP insertion in cardiac arrest patients with ACS doesn’t significantly affect Beclin-1 and Caspase-3 levels. Caspase-3 serum levels may predict mortality in these patients, with a sensitivity of 64% and a specificity of 66.7%.